Ta’līm al-‘Adad biṭ-Ṭarīqah al-Istiqrāiyyah bi Istikhdām Kitab “al-Qawā’id at-Taṭbīqiyyah fī al-Lugah al-‘Arabiyyah bi Ma’had at-Taqwā bi Atsyiyah asy-Syamāliyah - Kasyful Anwar; Aan Muhammady; Danil Zulhendra (Universitas Jabal Ghafur, 2023)
Nahwu science is the science of knowing the final state of a sentence in Arabic from the I'rab and bina perspectives. Understanding nahwu science is very important for anyone who wants to write and speak Arabic. There are three elements that influence someone to master Arabic, namely mufradat (vocabulary), Ashwat (sound) and Tarkib (structure). As for number material or in Arabic it is called 'Adad' which is one of several structures in nahwu science in terms of 'Tarkib or arrangement. The problem experienced by second-grade students at the at-Taqwa Islamic Boarding School is their inability to master number material. Therefore, it is expected that all teachers who teach nahwu lessons will use an appropriate method or book to make it easier for them to teach nahwu, namely the book “al-Qawa’id at-Taṭbiqiyyah fi al-Lugah al-‘Arabiyyah” which was compiled using the inductive. The purpose of this study was to determine the effectiveness of the book